DOT-1.1-dependent H3K79 methylation promotes normal meiotic progression and meiotic checkpoint function in C. elegans - Lascarez-Lagunas, Laura I. (PLoS Genet, 2020)
Epigenetic modifiers are emerging as important regulators of the genome. However, how they regulate specific processes during meiosis is not well understood. Methylation of H3K79 by the histone methyltransferase Dot1 has been shown to be involved in the maintenance of genomic stability in various organisms. In S. cerevisiae, Dot1 modulates the meiotic checkpoint response triggered by synapsis and/or recombination defects by promoting Hop1-dependent Mek1 activation and Hop1 distribution along unsynapsed meiotic chromosomes, at least in part, by regulating Pch2 localization. However, how this protein regulates meiosis in metazoans is unknown. Here, we describe the effects of H3K79me depletion via analysis of dot-1.1 or zfp-1 mutants during meiosis in Caenorhabditis elegans. We observed decreased fertility and increased embryonic lethality in dot-1.1 mutants suggesting meiotic dysfunction. We show that DOT-1.1 plays a role in the regulation of pairing, synapsis and recombination in the worm. Furthermore, we demonstrate that DOT-1.1 is an important regulator of mechanisms surveilling chromosome synapsis during meiosis. In sum, our results reveal that regulation of H3K79me plays an important role in coordinating events during meiosis in C. elegans.